Pengaruh Literasi Keuangan Terhadap Keputusan Investasi (Studi Kasus Mahasiswa Fakultas Ekonomi dan Bisnis UIN Jakarta) - Sovi Nuraini; Widad Nadia; Salwa Nabilah Putri; Yulyana Yulyana (Universitas 45 Surabaya, 2023)
The importance of planning before investing really needs to be considered by student, who do a lot of financial literacy. This can add knowledge and experience to minimizing the failure rate of businesses to expect future profits. The purpose of this study was to determine the effect of literacy activities with various sources in determining the attitude of investment decision making by students. This study uses primary data obtained from the result of disturbing questionnaires and is supported by literature studies. Data management uses the SPSS application whose results are analyzed and presented in the form of a description. The study population was undergraduate students of the Faculty of Economics and Busines, UIN Jakarta. While the research method using purposive sampling. So the result of this study indicate that the level of financial literacy does not directly affect the investment decisions of respondents, namely S1 Students of the Faculty of Economics and Business, UIN Jakarta.